(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
This contribute describes Ludovico Quaroni’s approach to Persian culture, his first visits to Persia and his first contacts with the academic environment of Tehran. Then, the text introduces the sequence of events which lead to the elaboration of the Yazd Masterplan by the “Design Atelier” of the Faculty of Architecture of the University of Tehran, established in 1962, and lead by Mehdi Kowsar, dean of the Faculty of Tehran, who involved Ludovico Quaroni for some consultancy and advisorship activities.